Kepastian Hukum, Kemanfaatan Dan Keadilan Pemidanaan Kejahatan Asal Usul Perkawinan: Analisis Putusan No. 387/Pid.B/2021/PN.Jmb - Fitrihabi, Nuraid; Rafikah, Rafikah; Kurniawan, Ardian (Al-Jinayah : Jurnal Hukum Pidana Islam, 2021)
The purpose of the law includes three elements: certainty, expediency, and justice. All three must be regarded asthe foundation for which the law is created not only of juridical value but also of philosophical and sociological value. This study aims to examine the decision of the Jambi District Court No. 387/Pid.B/2021/PN.Jmb which imposes imprisonment on polygamous perpetrators without the wife's and court's permission by considering the principles of legal certainty, benefit and justice. The research is normative legal research, with the object of study is legal principles accompanied by a case approach. The decision implies a conflict between legal certainty, the principle of justice, and the usefulness of the law, especially concerning the position of the convict. Therefore, justice in the court decision is considered partial, retributive justice, which is regarded as no longer relevant. Ideally, the punishment of the accused is accompanied by restitution to the victim by way of restorative justice, which is not only concerned with punishing and deterring the perpetrators but also about protecting the families as victims.